Agriculture in the northern region of Brazil: spillovers of technology among municipalities - Edi Flores Reyna; Rubicleis Gomes da Silva; Viviani Silva Lírio (Geosul, 2019)
This paper, about the northern agricultural sector, aims to verify the existence of the spillover effect of technology among the municipalities of the region, as well as to analyze the determinants of the production value of the agricultural sector in 2006. For this purpose, we used methods derived from spatial econometric. The findings showed that in the agricultural sector of the North the labor force has a greater impact on the value of production, and that there isn’t technology spillover among the municipalities. This outcome can be explained by the low-road-density in the region and by the distance between establishments, these factors don’t allow the dissemination and sharing of technology. However, we verified the existence of spatial dependence in the regression disturbance term in the northern agricultural sector.